Lulu and the hedgehog in the rain - McKay, Hilary (McKay, Hilary. LuLu, 2014)
"When Lulu rescues a wild hedgehog in a storm, she knows she can't keep it as a pet--it wants to roam free. So she and her cousin Mellie come up with the neighborhood Hedgehog Club to keep it safe"--